Strategi Pempek XYZ Memenangkan Pangsa Pasar Melalui Kualitas Produk - Herlina Herlina; Fitri Novi Windu; Eri Bestary Al Haitamy (Universitas Batanghari Jambi, 2023)
There are so many culinary business opportunities, one of which is pempek because apart from being easy to produce, it is also in great demand. This regional food has tough competition between producers. So novice business people who are in the pempek business, they need to present quality products. Pempek XYZ has been established for four years, market segmentation has not varied, packaging design features are still minimal, product variants are still the same as competitors, and promotions are still minimal, but they want wider market access to increase pempek sales revenue. This research aims to identify pempek XYZ market segmentation and product quality and develop a strategy to attract consumers by improving product quality. The method used is the interview. The analysis techniques are STP analysis (segmentation, targeting, position), eight dimensions of product quality analysis, and SWOT analysis. The results showed that the target market for pempek XYZ was not diverse, it was still the middle-income family. Product quality must be improved through improvements in packaging design, features, product variants, and product benefits. The strategy is to have distributors, agents, and retailers (salesmen), provide modified product information, complete halal features, BPOM permits, production and expiration dates, product storage recommendations, explanation of composition on the packaging, create bonus coupons, post as products not just filling and healthy but able to provide new experiences through the addition of variants and value of pempek XYZ in the form of facilities that will trigger consumers to continue to explore product features, explore many moments, explore tastes and explore packaging designs when consuming pempek.